How do Chinese tourists negotiate the constraints of engaging in post-COVID-19 domestic travel? - Haizhou Zhang; Shixiu Weng; Jigang Bao (Annals of Tourism Research Empirical Insights, 2022)
Post-COVID-19 domestic travel, a valuable component of tourism recovery, has been initiated. However, verified and detailed knowledge regarding epidemic-induced travel behaviour changes from an emic perspective is lacking. Focusing on actual behaviour based on a field investigation of Chinese domestic travellers, this study provides detailed knowledge of the travel constraint-negotiation interaction process between travellers and the epidemic. The findings suggest that the effects of COVID-19 involve various constraints including intrapersonal, interpersonal and structural factors at both the context and system levels. Both cognitive and behavioural strategies are synergistically used in an interlinking manner and depend not only on individual preference and self-efficacy but also, more importantly, on the temporality and socioculture of COVID-19 created by anti-epidemic practices.
Keywords: 330; Travel constraint; Negotiation strategy; Post-COVID-19 domestic travel; China